What is in a name: Taxonomy of speech sound disorders from a cross-linguistic perspective - Petinou, Kakia; Ttofari, Kerry; Filippou, Elma (My University, 2024)
In response to the call for papers under the theme "What is in a name" proposed by the Scientific Child Speech Committee of the International Association of Communication Sciences and Disorders (IALP), the current paper discusses taxonomy and its relation to speech sound disorders (SSD) from a cross-linguistic perspective.
Keywords: speech therapists; articulation; disorder; language therapists